Terapi Akupresur untuk Menurunkan Nyeri Pascaoperasi Jantung selama perawatan di RS: Sebuah Tinjauan Literatur - Anisa Muliyawati; Tuti Herawati; Riri Maria (Jurnal Ners, 2025)
Acute postoperative pain following cardiac surgery, typically localized in the thoracic region, can adversely affect cardiopulmonary function, inhibit effective coughing, and increase the risk of complications such as atelectasis and pneumonia, ultimately contributing to prolonged hospitalization. Multimodal pain management strategies incorporating acupressure—an intervention that modulates both the nervous and inflammatory systems—offer a non-pharmacological means of reducing pain perception and minimizing opioid requirements. This literature review aims to evaluate the effectiveness of acupressure therapy in managing postoperative pain among cardiac surgical patients. This study employed a literature review method by analyzing articles retrieved from databases including ScienceDirect, PubMed, and Scopus, published between 2015 and 2024. The review revealed that six out of seven studies reported that acupressure therapy significantly reduced pain levels in postoperative cardiac patients. Therefore, acupressure can be considered a complementary intervention in managing postoperative pain in cardiac patients.